1996
DOI: 10.1021/jp9603804
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effects on Long Living ZEKE States

Abstract: The effect of an electric field on the overall intensity of the ZEKE spectrum and on the lifetime is discussed for very long living states detected by a pulsed field ionization delayed by several microseconds or more. It is shown that the presence of a dc electrical field can shorten the very long lifetimes and that it can also reduce the overall intensity of the very long living states. The decrease in the long lifetimes of the ZEKE states is complementary to the field-induced elongation of the shorter lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…ZEKE (zero electron kinetic energy) spectroscopy has provided valuable insight into the dynamics of high atomic and molecular Rydberg states. In ZEKE spectroscopy, the lifetimes of high Rydberg states have been found to be orders of magnitude longer than what was expected by extrapolating the lifetimes at low n using an n 3 scaling law and extremely sensitive to external perturbations such as an external dc field, an external magnetic field, or the presence of neighboring ions. The role of the external dc field in diluting the coupling strength to the decay channels over the entire l manifold and increasing the lifetime was early on pointed out by Bordas and Chupka , and then studied in more detail. The lifetimes of high molecular Rydberg states are also considerably enhanced by collisional effects and the presence of a magnetic field. ,,, Moreover, experimentally, the decay kinetics of the ZEKE intensity very often exhibits a bimodal character, ,, with a prompt and a delayed component. This bimodal decay of the ZEKE intensity was also recovered theoretically both from a kinetic model and from dynamical computations. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZEKE (zero electron kinetic energy) spectroscopy has provided valuable insight into the dynamics of high atomic and molecular Rydberg states. In ZEKE spectroscopy, the lifetimes of high Rydberg states have been found to be orders of magnitude longer than what was expected by extrapolating the lifetimes at low n using an n 3 scaling law and extremely sensitive to external perturbations such as an external dc field, an external magnetic field, or the presence of neighboring ions. The role of the external dc field in diluting the coupling strength to the decay channels over the entire l manifold and increasing the lifetime was early on pointed out by Bordas and Chupka , and then studied in more detail. The lifetimes of high molecular Rydberg states are also considerably enhanced by collisional effects and the presence of a magnetic field. ,,, Moreover, experimentally, the decay kinetics of the ZEKE intensity very often exhibits a bimodal character, ,, with a prompt and a delayed component. This bimodal decay of the ZEKE intensity was also recovered theoretically both from a kinetic model and from dynamical computations. …”
Section: Introductionmentioning
confidence: 99%
“…The role of the external dc field in diluting the coupling strength to the decay channels over the entire l manifold and increasing the lifetime was early on pointed out by Bordas 25 and Chupka 26,27 and then studied in more detail. [28][29][30][31][32][33][34][35][36][37] The lifetimes of high molecular Rydberg states are also considerably enhanced by collisional effects and the presence of a magnetic field. 3,15,18,[38][39][40][41][42][43][44] Moreover, experimentally, the decay kinetics of the ZEKE intensity very often exhibits a bimodal character, 17,45,46 with a prompt and a delayed component.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,[17][18][19] Numerous studies have shown evidence of Rydberg-Rydberg coupling involving transfer of energy and angular momentum between Rydberg-orbital and core-rovibrational degrees of freedom, [20][21][22][23][24][25][26][27][28] but most workers now agree that the dominant mechanism for lifetime lengthening lies in the field-induced evolution of the Rydberg electronic degree of freedom in the nonpenetrating space of high l and m l . [29][30][31][32] In earlier work, we used three-color rovibrational selection to study the ZEKE spectrum of NO 2 in strong vertical 3pσ Rydberg-to-threshold transitions. 33 Our results characterized the rotational and vibrational structure of the cation, including a moderate bend-stretch Fermi resonance, 34 which is present to virtually the same degree in the cation core of the originating 3pσ Rydberg state.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is consistent with the observation that the discrete structure observed in the spectra below n = 80 corresponds to a purely hydrogenic Rydberg series with zero quantum defect (see also discussion in Refs. [41][42][43][44]).…”
Section: Determination Of Autoionization Ratesmentioning
confidence: 99%